PERAN ETNIS PEMILIK USAHA SEBAGAI PEMBEDA TANGGUNG JAWAB RELASIONAL PADA KEPUTUSAN PEMBELIAN - LUSSIA MARIESTI ANDRIANY (AKADEMIKA, 2018)
This study aims to reveal the ethnic influence of business owners on purchasing decisions as well as on the relationship between relational responsibility and purchasing decisions. The ethnic groups chosen as distinctions are the Chinese, Arabs and Madura based on the fact that trade in Indonesia is dominated by the three ethnic groups. This research use surevi method using questionnaire. Respondents of the study amounted to 105 buyers representing the three ethnic groups. Data were analyzed through two stages, namely confirmatory factor and regression analysis with dummy variable. Based on the results of data analysis, it is known that the ethnic business owner is not a variable that distinguishes the decision of someone buying in a particular store. However, it is a variable that distinguishes relational responsibility relationships on purchasing decisions on ethnic Chinese, Arab and Madura-owned businesses.